Agile Processes in Software Engineering and Extreme Programming 13th International Conference, XP 2012, Malmö, Sweden, May 21-25, 2012, Proceedings - Wohlin, Claes.; Wohlin, Claes. (Lecture Notes in Business Information Processing,, 2012)
This book contains the refereed proceedings of the 13th International Conference on Agile Software Development, XP 2012, held in Malmö, Sweden, in May 2012. In the last decade, we have seen agile and lean software development strongly influence the way software is developed. Agile and lean software development has moved from being a way of working for a number of pioneers to becoming, more or less, the expected way of developing software in industry. The topics covered by the selected full papers include general aspects of agility, agile teams, studies related to the release and maintenance of software, and research on specific practices in agile and lean software development. They are complemented by four short papers capturing additional aspects of agile and lean projects.